Barriers and facilitators to physical and mental health help-seeking among Congolese male refugee survivors of conflict-related sexual violence living in Kampala - Kansiime, Peninah (Stellenbosch : Stellenbosch University, 2017)
Thesis (M.Phil)--Stellenbosch University, 2018.